Impact of team‐based care on appropriate statin therapy prescribing in ***HIV‐infected patients. Issue 3 (28th January 2020) - Hester, Elizabeth K.; Caulder, Celeste R.; Penzak, Scott R.
Abstract: Introduction: Statins have historically been underutilized in patients living with ***HIV infection (PLWH) despite reported rates of cardiovascular disease twice that of the general population. Objective: To evaluate the impact of team‐based pharmacy services on appropriate statin prescribing compared with standard care in an HIV primary care clinic. Methods: A retrospective chart review of adult PLWH was conducted for appropriate statin prescribing according to 2013 American College of Cardiology/American Heart Association cholesterol guidelines. Patient outcomes were stratified by team‐based care defined as physician/pharmacy collaboration, and standard care defined as primary care without clinical pharmacy services. The primary outcome was the percentage of patients receiving appropriate statin therapy in the two groups. Secondary outcomes included percentage of patients receiving appropriate statin therapy, number of patients indicated for therapy but untreated, and achievement of low‐density lipoprotein (LDL) goal reduction. Chi‐square analysis was used for nominal comparisons, and logistic regression was used to identify predictors of appropriate statin prescribing. Results: Three hundred fifty‐two charts were screened, 114 of which met inclusion criteria. Eighty‐nine patients (61%) received team‐based care and 25 (22%) received standard care. Appropriate statin prescribing was observed in a greater percentage of patients in the team‐based care group compared with the standard care group (86% vs 54%, respectively; P < .001). More patients receiving team‐based care were also prescribed statin therapy when indicated (98% vs 88%; P < .001). Team‐based care was a predictor of appropriate statin prescribing (odds ratio 10.31, P < .001); however, LDL goal reduction was achieved in <30% in both groups. Conclusion: Patients living with HIV infection receiving team‐based care that included a clinical pharmacist were significantly more likely to be prescribed appropriate statin therapy compared with patients receiving standard care. Nonetheless, achieving goal LDL reduction remained a challenge in these patients regardless of approach to care (team‐based vs standard).